Imaging in inflammatory bowel disease: current and future perspectives. Issue Volume 13:Issue e1(2022) (2nd June 2022) - Shaban, Nader; Hoad, Caroline L; Naim, Iyad; Alshammari, Meshari; Radford, Shellie Jean; Clarke, Christopher; Marciani, Luca; Moran, Gordon
Abstract : The use of cross-sectional imaging and ultrasonography has long complemented endoscopic assessment of inflammatory bowel disease (IBD). Clinical symptoms alone are often not enough to assess disease activity, so a reliance on non-invasive techniques is essential. In this paper, we aim to examine the current use of radiological modalities in aiding the management of patients with IBD. We focus on the various sections of the gastrointestinal tract and how different modalities can aid in assessing current disease state and response to treatments. We also have a look at how newer sequences in cross-sectional imaging and ultrasonography can allow for better differentiation of disease activity (ie, fibrotic vs inflammatory) as well improve evaluation of small bowel, colonic and perianal disease. Furthermore, we examine how advanced image processing has the potential to allow radiology to be a surrogate for biomarkers. An example of this is explored when reviewing the ability of MR sequences to quantify visceral fat, which potentially plays a role in determining disease activity in Crohn's disease. Lastly, we look into the expected role for artificial intelligence to be used as an adjunct to radiology to better improve IBD evaluation.